NEGATIVE PRESSURE WOUND THERAPY (NPWT) FOR THE MANAGEMENT OF DIABETIC FOOT WOUND - Wesiana Heris Santy (Universitas Nahdlatul Ulama Surabaya, 2015)
Complications often experienced by people with diabetes are complications in the feet ( 15 % ) called diabetic foot ( Akhtyo , 2009) . Where the injury to the leg if not treated properly will lead to infections and ultimately need to be amputated .The purpose of writing articles is to review and discuss the evidence-based literature bersadarkanpraktice of Negative Pressure Wound Therapy Effectiveness ( NPWT ) ) on the healing of diabetic foot ulcers.One technology that is used to prevent and avoid lower limb amputation is the technique of negative pressure or Negative Pressure Wound Therapy ( NPWT ) ) . This negative pressure technique has grown rapidly and now has been widely used in many countries , especially in Western European countries ( Germany ) and the United States . Negative pressure technique has the advantage that it is relatively cheaper cost than the use of hyperbaric oxygen . Results obtained by several studies that the use of NPWT may improve wound healing process through efforts to create a moist wound environment and decrease edema that becomes optimal wound healing , throw that out of the wound exudate so that the protease enzyme in the exudate also go wasted , this enzyme is known to interfere wound healing process . The other benefit is that it can stimulate cell growth by increasing angiogenesis physically , so that the growth of new cells will be maximal   Abstrak : Komplikasi sering dialami pengidap diabetes adalah komplikasi pada kaki (15% ) disebut kaki diabetes (Akhtyo, 2009).Dimana luka pada kaki jika tidak ditangani dengan baik akan menyebabkan terjadinya infeksi dan akhirnya perlu di amputasi. Tujuan penulisan artikel adalah mengkaji dan membahas literature bersadarkan evidence based praktice  tentang Efektifitas Negative Pressure Wound Therapy (NPWT)) pada penyembuhan ulkus kaki Diabetik. Salah satu teknologi yang digunakan untuk mencegah dan menghindari amputasi ekstremitas bawah adalah  teknik tekanan negatif atau Negative Pressure Wound Therapy (NPWT)). Teknik tekanan negatif ini telah berkembang dengan pesat dan sekarang ini telah banyak digunakan di berbagai negara, terutama di negara Eropa Barat (Jerman) dan Amerika Serikat. Teknik tekanan negatif mempunyai keuntungan yaitu biaya relatif lebih murah dibandingkan penggunaan hiperbarik oksigen.Hasil yang diperoleh berdasarkan beberapa penelitian yaitu  penggunaan NPWT dapat meningkatkan proses penyembuhan luka melalui  upaya penciptaan lingkungan luka yang lembabdanmenurunkan edema sehingga penyembuhan luka menjadi optimal, membuang eksudat yang keluar dari luka sehingga enzim protease di dalam eksudat juga ikut terbuang, enzim ini diketahui mengganggu proses penyembuhan luka. Manfaat lainnya yaitu dapat menstimulasi pertumbuhan sel secara fisik dengan meningkatkan angiogenesis, sehingga pertumbuhan sel baru akan maksimal.